Monitoring Networks Based on Simple Network Management Protocol With Cacti Application and Telegram Notifications on Linux Ubuntu - Zikra, Fauzan; Anwar, Anwar; Safar, Ilham (Politeknik Negeri Lhokseumawe, 2026)
This study discusses the implementation of SNMP-based network monitoring with tools such as Cacti, Telegram, and The Dude. A common problem in networks is damage to router interfaces. In this study, notifications of problematic interfaces and bandwidth usage are sent via Telegram. The main objectives of this network monitoring are to monitor network stability, bandwidth usage, remote device monitoring, and to detect problems with interfaces. Cacti is used to monitor and analyze network performance. Telegram plays a role in receiving notifications related to problematic interfaces and bandwidth usage. Meanwhile, The Dude is used to automatically monitor and manage network devices by detecting connected devices. This study uses four routers and one server in i ts implementation. This monitoring focuses on interfaces that manage network distribution and data traffic. The results of this study show that on August 14, 2023, from 14:00 to 17:20, bandwidth measurements from the Cacti and Graphing charts. For inbound traffic, the maximum value on ether1 (CORE) with the Cacti application was 10.27 Mbps and on Graphing it was 11.56 Mbps with a difference of 1.29 Mbps. In comparing the maximum values for inbound traffic, the difference between the data obtained from Cacti and Graphing ranged from only 3.2% to 12.9%. This demonstrates the accuracy of the monitoring tools used in this study.